Deflection of beam / Fadzli Mohammad Ngimriti, Hurul Ain Abdul Nasher and Haryana Adam - Mohammad Ngimriti, Fadzli; Abdul Nasher, Hurul Ain; Adam, Haryana (Faculty Of Mechanical Engineering, 2003)
The FL160 is designed to examine the bending of cantilevers. It enables experiments to be performed in relation to pure bending, cross bending, oblique bending and shear center. The relatively complex theory of beam bending can thus be appropriately supplemented by way of experimental results. The horizontal arrangement of the specimen beam produces a clear-out, readily understandable test set-up. The deflection of the beam can be observed from the end face, thus clearly illustrating the relationship between load plane, principle axes and deflection/torsion. The system is suitable both for lecture-theatre demonstration and for practical experimentation in small group.